Pengaruh Corporate Social Responsibility & Debt to Equity Ratio terhadap Nilai Perusahaan - Adelia, Rafa Caroline; Fajriana, Icha (MDP Student Conference, 2024)
The point of this inquire about is to look at and analyze the relationship between corporate social duty and obligation to value proportion on company esteem. This investigate employments auxiliary information, specifically money related reports and yearly reports. This investigate studied 23 nourishment and refreshment companies recorded on the IDX between 2020-2022. The testing procedure utilized was purposive testing. Inquire about information was analyzed utilizing different direct relapse investigation. The investigate comes about appear that corporate social duty and obligation to value proportion have a critical impact on company esteem.